IAALD meets in Dakar - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The International Association of Agricultural Information Specialists (IAALD) will hold its 10th world congress- its first in Africa - in Dakar, Senegal, 24-28 January 2000 on 'Challenges Facing the Community of Agricultural Information...